Team Effectiveness Intervention Using TeamSTEPPS in Healthcare: A Literature Review - Rosa DM., Rizka; Yuanasika, Dwiky (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
In healthcare, effective teamwork and communication are essential. Medical errors are prevalent because there is a lack of a patient safety culture. This article's goal is to highlight TeamSTEPPS interventions that improve team effectiveness in the healthcare industry. Using Google Scholar, Science Direct, and PubMed with restrictions for the years 2018 through 2023, a review of published articles was conducted. In order to assess the efficacy of TeamSTEPPS, the six studies under consideration used a variety of instruments, including the Hospital Survey of Patient Safety Culture Questionnaire, the Short Assessment of Patient Satisfaction Scale, the Nursing Culture Assessment Tool, and the Patient's Adverse Events Questionnaire. The TeamSTEPPS program's interprofessional participants demonstrated improved coordination, cooperation, and communication between healthcare professionals. As a result, it is important to make the TeamSTEPPS program sustainable and part of the culture of health services